Solvent mimicry with methylene carbene to probe protein topography - Gomez, Gabriela Elena (2015)
The solvent accessible surface area (SASA) of the polypeptide chain plays a key role in protein folding, conformational change, and interaction. This fundamental biophysical parameter is elusive in experimental measurement. Our approach to this problem relies on the reaction of the minimal photochemical reagent diazirine (DZN) with polypeptides. This reagent (i) exerts solvent mimicry because its size is comparable to water and (ii) shows scant chemical selectivity because it generates extremely reactive methylene carbene. Methylation gives rise to the EM (extent of modification) signal, which is useful for scrutinizing the conformational change triggered by Ca2+ binding to calmodulin (CaM). The increased EM observed for the full protein is dominated by the enhanced exposure of hydrophobic area in Ca2+-CaM. Fragmentation allowed us to quantify the methylene incorporation at specific sites. Peptide 91–106 reveals a major reorganization around the calcium 151 binding site, resulting in local ordering and a greater exposure of the hydrophobic surface. Additionally, this technique shows a high sensitivity to probe recognition between CaM and melittin (Mel). The large decrease in EM indicates the occlusion of a significant hydrophobic area upon complexation. Protection from labeling reveals a larger involvement of the N-terminal and central regions of CaM in this interaction. Despite its smaller size, Mel’s differential exposure can also be quantified. Moreover, MS/MS fragmentation realizes the goal of extending the resolution of labeled sites at the amino acid level. Overall, DZN labeling emerges as a useful footprinting method capable of shedding light on physiological conformational changes and interactions.